2016
DOI: 10.1136/lupus-2016-000145
|View full text |Cite
|
Sign up to set email alerts
|

CR1 exon variants are associated with lowered CR1 expression and increased susceptibility to SLE in aPlasmodium falciparumendemic population

Abstract: BackgroundComplement receptor 1 (CR1) plays an important role in immune complex clearance by opsonisation and possibly protects subjects from development of autoantibodies. Lower CR1 expression has been associated with susceptibility to systemic lupus erythematosus (SLE). In contrast, subjects displaying lower CR1 expression are protected against severe manifestations of falciparum malaria. This study is the first of its kind to investigate the association of CR1 variants with development of SLE in a P. falcip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, in an earlier observation, we have demonstrated protection against severe malaria and malarial death in complement receptor 1 variants and concluded a possible reason for higher prevalence of CR1 mutants in malaria endemic areas 14 . We had also observed that CR-1 mutants are susceptible to development of SLE and lupus nephritis since they expressed lower surface CR1 which affects clearance of apoptotic debris 73 . Furthermore, similar association of FcγRIIb variant (codon 232) with susceptibility to SLE and protection against P .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in an earlier observation, we have demonstrated protection against severe malaria and malarial death in complement receptor 1 variants and concluded a possible reason for higher prevalence of CR1 mutants in malaria endemic areas 14 . We had also observed that CR-1 mutants are susceptible to development of SLE and lupus nephritis since they expressed lower surface CR1 which affects clearance of apoptotic debris 73 . Furthermore, similar association of FcγRIIb variant (codon 232) with susceptibility to SLE and protection against P .…”
Section: Discussionmentioning
confidence: 94%
“…Gender wise analysis has been recommended in numerous earlier reports of genetic association studies 73,75,76 . SLE is a chronic inflammatory autoimmune disorder and mostly prevalent in females 77 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to being an antigen with a lower frequency in Europe, it has been reported in several publications that CR1 p.His1208Arg is correlated with low CR1 cell surface expression. 11,12 We therefore speculated that our failure to detect anti-CR1 p.1208Arg in the inhibition assay was because we needed homozygous CR1 p.1208 (Arg/Arg) RBCs for a reaction in the IAT.…”
Section: Anti-cr1 P1208argmentioning
confidence: 99%
“…Studies in humans revealed erythrocyte complement receptor 1 (E-CR1) density polymorphisms, which vary by ethnic group (Panda, Ravindran & Das, 2016). Three polymorphic phenotypes, related to the expression levels of CR1 on erythrocytes, exist in Caucasian (Opi et al, 2016) subjects.…”
Section: Introductionmentioning
confidence: 99%